Salience and cooperation among rational egoists - Raul V. Fabella (University of the Philippines, School of Economics (UPSE), 2013)
We fuse a social dilemma game and a game pitting the group against nature, where the group's probability of avoiding disaster depends on the resources it raises from members. The result is the Nederlander-Prisoner's Dilemma Game where the cost of failure is equally shared. We introduce the concept of the Ostrom threshold, the failure cost in excess of which cooperation is best reply to itself. We give the condition for the existence of the Ostrom threshold in the Nederlander-Prisoner's Dilemma Game. For high enough cost of failure, cooperation among rational egoists is sustained. The Ostrom threshold first rises and then falls as the fury of nature rises.
Keywords: C72; D01; D02; 330; social dilemma; rational egoist; cooperation; Ostrom threshold